2022
DOI: 10.1186/s12879-022-07716-5
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent or standard plasma versus standard of care in the treatment of COVID-19 patients with respiratory impairment: short and long-term effects. A three-arm randomized controlled clinical trial

Abstract: Background The efficacy of early treatment with convalescent plasma in patients with COVID-19 is debated. Nothing is known about the potential effect of other plasma components other than anti-SARS-CoV-2 antibodies. Methods To determine whether convalescent or standard plasma would improve outcomes for adults in early phase of Covid19 respiratory impairment we designed this randomized, three-arms, clinical trial (PLACO COVID) blinded on interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…A statistically significant low in the median expected absolute difference was observed in studies with a favorable outcome [21,28] compared to those with an unfavorable outcome [7,12,15,18,22,38,39,45,46] (20.0% versus 33.9%, p = 0.04).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A statistically significant low in the median expected absolute difference was observed in studies with a favorable outcome [21,28] compared to those with an unfavorable outcome [7,12,15,18,22,38,39,45,46] (20.0% versus 33.9%, p = 0.04).…”
Section: Resultsmentioning
confidence: 89%
“…After the exclusion of 130 records, 94 full-text articles were identified and assessed for eligibility, resulting in the selection of 48 RCTs. Finally, after the exclusion of 16 RCTs (see Supplementary Table S1 for the reasons for their exclusion), 32 RCTs [7,8,10,[12][13][14][15][16][17][18][20][21][22]25,26,28,[30][31][32]34,35,[37][38][39]41,43,[45][46][47][48][49]51] were included in the systematic review. The study selection process is summarized in the PRISMA flow diagram in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“… 28–32 A randomized study reported no effect on clearance of viraemia with three units of convalescent plasma ( n = 60) compared with standard of care ( n = 60). 33 In contrast, one unit of convalescent plasma was administered daily until serum viral clearance at our study hospital, which may explain a difference between these studies. It is, however, important to note that results from this study were incidental findings and that the study was primarily designed to investigate the effect of remdesivir and not convalescent plasma treatment.…”
Section: Discussionmentioning
confidence: 87%
“…For the 28-day main cohort, 34 randomized controlled trials were included [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. For the 14-day secondary cohort, 10 articles on randomized controlled trials provided the necessary data.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 34 studies were included in the overall meta-analysis for the 28-day cohort [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The effect outcome for 28-day mortality was not statistically significant [RR = 1.00, 95% C.I.…”
Section: Resultsmentioning
confidence: 99%